Phylogenetic relationships of a new species of Apostolepis from Brazilian Cerrado with notes on the assimilis group (Serpentes: Colubridae: Xenodontinae: Elapomorphini) - Ferrarezzi, Hebert; Barbo, Fausto Erritto; Albuquerque, Cristina España (Papéis Avulsos de Zoologia, 2005)
The assimilis species group is one of the several assemblages that can be distinguished within the genus Apostolepis. The group is characterized by a uniform red dorsal pattern, broad nucho-cervical collars, enlarged light snout blotch, dark ventral head, and entirely black terminal shield. A new species is here recognized as a member of the assimilis group and its phylogenetic relationships to A. assimilis and A. cearensis is inferred by means of cladistic analysis. Apostolepis ammodites sp. nov. can be easily diagnosed from all congeners by many autapomorphies and an exclusive combination of features. Comparative data are presented on scalation, coloration, dentition, osteology, and geographic distribution, with some notes on feeding and reproductive biology. The new species occurs through central Brazilian Cerrado, filling a gap between the areas occupied by A. assimilis and A. cearensis. Although superficially resembling A. assimilis, parsimony analysis based on morphological data indicates its phylogenetic relationships closest to A. cearensis. Systematic analysis shows that two recently described species, A. freitasi and A. tertulianobeui, must be relegated as junior synonymies of A. cearensis and A. assimilis, respectively.